Representations of Religion and Culture in Children's Literature. An Analysis of othering Processes in Texts and Illustrations Representations of Religion and Culture in Children's Literature - Verena Marie Eberhardt (Journal for Religion, Film and Media, 2018)
Literature is an important medium for representing and communicating world views and values. This article focuses on the representation of culture and religion and reveals constructions of identities in children's literature. The analysis of selected contemporary books from the German speaking area considers the representation of the main characters and their cultural and religious background as well as their faith and practices with a discourse analytical approach. The analysed narrations tend to specify difference by means of cultural and religious characteristics; instead of dissolving those categories, narrations strengthen them. The article states the importance of literature in the mediation of knowledge, self-concepts, interpersonal perceptions and normative paradigms.